Organic agriculture in Tunisia, Africa - (:unkn) unknown (My University, 2024)
Tunisia reports 279,389 hectares of certified organic agriculture, accounting for 2.87% of the country’s farmland. Most of Tunisia’s organic production is exported. Organic olive oil accounts for 74% of organic exports, and organic dates for 22%. In 2021, Tunisia bid and won the right to host the Organic World Congress (OWC) 2024. After almost half a century of OWCs, the prospective OWS Tunis 2024 was to be the first such event to be held in Africa. It would be an opportunity to showcase Tunisian and African organics, and to provide a welcome impetus to grow the organics sectors of the country and the continent. In 2023, OWS Tunis 2024 was cancelled in the wake of the Covid-19 pandemic, the loss-making OWC Rennes 2021, and changed economic, political and social circumstances. The African continent is an under-performer in organics; 15 countries report no organics, 28 countries report less than 1% organics and only a single country reports greater than 5% (viz. São Tomé and Principe, 21.2%). Tunisia is an organics leader in Africa. The present paper tracks the stop-start growth of the organics sector of Tunisia over the past two decades.
Keywords: African Research